On the Outcomes and Lessons of Russia’s Chairmanship of the Arctic Council (2021–2023) - Valery P. Zhuravel; Diana S. Timoshenko (Арктика и Север, 2023)
The article summarizes the results of Russia’s chairmanship in the Arctic Council (AC, Council) in 2021–2023, analyzes the relationship with the state national and international policy, and systematizes the key results. The authors identify four main periods of Russian chairmanship. The article presents general logical, theoretical, and empirical research methods. It is noted that due to the boycott of a number of Western countries because of the events in Ukraine, the Russian Federation focused its efforts in the Arctic direction on the northern territories of the country and was able to achieve certain successes. Russia has carried out most of the planned activities related to economic and social development, climate change, ecology, human capital, indigenous peoples’ activities, tourism, and prevention of emergency situations in the Arctic. The “Arctic Youth” direction well represented, and a large number of projects for youth events and career guidance were launched. The conclusion is made: during the 2-year period the government paid special attention to improving the functioning of the Northern Sea Route, socio-economic development of the Arctic regions of the Russian Federation, but due to the geopolitical situation Russia failed to fully realize its plans. The authors note that the course of the chairmanship was internally incomplete, especially during the recent periods. The remote transfer of the chairmanship of the Arctic Council to Norway raises many questions. It is hoped that the full status and composition of the AC will be restored. Russia still proceeds from the fact that the pressing problems of the Arctic region can be solved only through balanced and mutually beneficial international co-operation.